The Performance Of The Internal Auditors Of The Village Rural Institution - Komang Adi Kurniawan SAPUTRA (International Journal of Environmental, Sustainability, and Social Science, 2020)
This study aims to examine the influence of competence variables, coordination and task complexity on the performance of internal regulatory bodies as internal auditors at Lembaga Perkreditan Desa. Research respondents are managers who understand all the policies and governance of the organization that is the leader of the organization. The number of samples in this study was 63 using purposive sampling sampling technique. Hypothesis testing using statistical analysis of multiple regression or ordinary least square with the result of research is competence, coordination and task complexes have a significant positive effect on the performance of regulatory body as internal auditor of rural institution in Buleleng regency of Bali.